Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004696.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Calorie and protein-enriched formula versus standard term formula for improving growth and development in preterm or low birth weight infants following hospital discharge

Abstract: The limited available data do not provide strong evidence that feeding preterm or low birth weight infants following hospital discharge with calorie and protein-enriched formula compared with standard term formula affects growth rates or development up to 18 months post-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
0
18
0
2
Order By: Relevance
“…The frequency was determined by an estimation, from 7-14% in 1999-2000 period. If the proportion of child-bearing mothers is 2.5% of the total population, there will be 355,000-710,000 low birthweight infants out of 5 million newborn infants (Henderson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency was determined by an estimation, from 7-14% in 1999-2000 period. If the proportion of child-bearing mothers is 2.5% of the total population, there will be 355,000-710,000 low birthweight infants out of 5 million newborn infants (Henderson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, Decurtis et al 20 and the Cochrane Database 21 conclude that the evidence is limited that feeding preterm infants after hospital discharge with a calorie and protein-enriched formula (compared to a standard term formula) leads to a higher rate of linear growth and weight gain. 21 The 33 patient Decurtis trial 20 is a 2-month study and is among the six trials 15,16,18,20,22 meeting inclusion in the Cochrane analysis.…”
Section: Introductionmentioning
confidence: 99%
“…21 The 33 patient Decurtis trial 20 is a 2-month study and is among the six trials 15,16,18,20,22 meeting inclusion in the Cochrane analysis. Based on these six studies they recommend that follow-up of infants participating in the trials might provide further data on the effect of the intervention and growth through later childhood and on later neuro developmental outcomes, also concluded that large randomized controlled trials are needed.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 No added benefit of this was noted on neurodevelopment. 23,24 Preterm infants may be transitioned off of highly enriched preterm formula and started on transitional formula at approximately 2,000 g if they are not fluid restricted. Preterm formulas may be used up to 3,000 g. 25 Iron (2 mg/kg/day) should be given as a supplement to preterm infants receiving unfortified human milk up until age 12 months, 7 but supplementation with multivitamins is controversial.…”
Section: Nutritionmentioning
confidence: 99%